Peran Politik Hukum Dalam Pemberantasan Tindak Pidana Korupsi DiIndonesia - Stefanus Wahyu M.J; Fernanda M.A; Satya Triwardani; Dwi Puspita S; Hidayatul Fattah (Wijayakusuma Law Review, 2023)
Corruption is an unlawful act which is opposed by all parties and can harm a country's economy. Corruption can becarried out in all aspects of society, from the lower classes to the upper classes. Corruption has become a legal issuewhich is complicated to deal with, because corruption is related to political, economic, and socio-cultural aspects,which can endanger the stability, security of the state and its people. However, in the matter of corruption, it mustbe realized that it is not a matter of the large amount of state losses, or the increasingly sophisticated corruptmodus operandi or Indonesia's ranking as one of the countries with the most corruption, but the fact that thedifficulty of eradicating corruption in Indonesia is revealed due to the powerlessness of law enforcement officials.in dealing with corruption cases. Legal politics is understood as choices regarding laws or regulations that areenforced and are intended to achieve state goals as stated in the Preamble to the Constitution of the 1945Constitution of the Republic of Indonesia. The direction of legal politics for eradicating corruption should have tobe continuously reflected and evaluation, whether the legal politics produces policies and legal products that arethe ideals of the nation, or turn out to be an obstacle to the nation's aspirations to achieve prosperity. This studyaims to find out how the application of legal politics in Indonesia in eradicating corruption and what factorshinder legal politics in eradicating corruption in Indonesia. The approach method used in this study is thenormative juridical approach which is carried out by examining library materials, namely books, journals, officialarticles exploring legal doctrines and theories from various literature and applicable laws and regulations. relatedto the issues discussed. The results of this study state that corruption is not just a legal symptom but is part of thepolitical system, therefore it is impossible to separate efforts to eradicate corruption from structuring the politicalsystem related to legal politics.